2011
DOI: 10.1073/pnas.1113651108
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative assembly and dynamic disassembly of MDA5 filaments for viral dsRNA recognition

Abstract: MDA5, an RIG-I-like helicase, is a conserved cytoplasmic viral RNA sensor, which recognizes dsRNA from a wide-range of viruses in a length-dependent manner. It has been proposed that MDA5 forms higher-order structures upon viral dsRNA recognition or during antiviral signaling, however the organization and nature of this proposed oligomeric state is unknown. We report here that MDA5 cooperatively assembles into a filamentous oligomer composed of a repeating segmental arrangement of MDA5 dimers along the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
312
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(350 citation statements)
references
References 32 publications
18
312
0
3
Order By: Relevance
“…Third, given that filament formation is inhibited by the ATPase activity of MDA5 (8), and that ATPase-deficient mutants of MDA5 exhibit constitutive signaling in cells (18), filaments-or filamentlike structures-may be involved in signaling. Similarly, a natural partial loss-of-function mutant in the MDA5 CTD (I923V) reduces binding cooperativity and filament formation in vitro (9) while reducing signaling in vivo (19,20), supporting a physiological role for filaments in signaling. The discovery that MDA5 polymerizes into helical filaments along dsRNA supports a signal transduction mechanism in which the helical array of MDA5 CARDs on the outside of MDA5-RNA filaments recruits MAVS and nucleates its assembly into an active fibril form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, given that filament formation is inhibited by the ATPase activity of MDA5 (8), and that ATPase-deficient mutants of MDA5 exhibit constitutive signaling in cells (18), filaments-or filamentlike structures-may be involved in signaling. Similarly, a natural partial loss-of-function mutant in the MDA5 CTD (I923V) reduces binding cooperativity and filament formation in vitro (9) while reducing signaling in vivo (19,20), supporting a physiological role for filaments in signaling. The discovery that MDA5 polymerizes into helical filaments along dsRNA supports a signal transduction mechanism in which the helical array of MDA5 CARDs on the outside of MDA5-RNA filaments recruits MAVS and nucleates its assembly into an active fibril form.…”
Section: Resultsmentioning
confidence: 99%
“…RNA binding through the helicase domain and CTD (5, 6) releases the CARDs, which then recruit unanchored lysine 63-linked polyubiquitin chains and activate the signaling adaptor mitochondrial antiviral-signaling protein (MAVS, also called interferon-β promoter stimulator 1, or IPS-1) (7). In contrast, MDA5 does not sequester its CARDs (8) and cooperatively assembles into ATP-sensitive filaments on dsRNA (8,9). Moreover, the MDA5 CTD is required for cooperative filament assembly, but not for RNA binding (8,10,11).…”
mentioning
confidence: 99%
“…In contrast to the previous model in which IFI16·dsDNA complexes resemble noninteracting beads on a string (9), our binding experiments suggested that IFI16 assembles into distinct oligomeric clusters on dsDNA. These two models can be distinguished by monitoring formation of FAM-dsDNA·IFI16 complexes in the presence of increasing amounts of unlabeled DNA using native gel electrophoretic mobility-shift assays (EMSAs): the clustering mechanism would show a concerted transition without resulting in significant intermediates, whereas the noninteracting mechanism would clearly display intermediate species (25,26). We first performed EMSAs with various FAM-dsDNA fragments.…”
Section: Resultsmentioning
confidence: 99%
“…Conventionally, assembling filaments on foreign nucleic acids has been considered as a defense strategy reserved for sensing intracellular RNA (28,42). For example, a principal mechanism by which melanoma differentiation associated protein (MDA)5 distinguishes self-from nonself-RNA is via cooperatively assembling into filaments along the length of long dsRNA with its two CARDs forming clusters tracing the center of filaments in a helical trajectory (25,26,(42)(43)(44)(45). IFI16 and MDA5 are unrelated proteins, and, not surprisingly, mechanisms allowing these proteins to assemble into filaments are significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…We found that MDA5 assembles into linear filaments along the length of dsRNA and that this filament formation is required for antiviral signal activation as it promotes oligomerization of the signaling domain, caspase activation recruitment domain (CARD) [4,5]. Furthermore, filament formation allows MDA5 to regulate its interaction with dsRNA according to the length of dsRNA as it disassembles from filament termini during ATP hydrolysis [6].…”
mentioning
confidence: 99%